Improving the Interfacial Bond Properties of the Carbon Fiber Coated with a Nano-SiO2 Particle in a Cement Paste Matrix - Gwang-Hee Heo; Jong-Gun Park; Ki-Chang Song; Jong-Ho Park; Hyung-Min Jun (Advances in Civil Engineering)
To improve the interfacial bond properties of the carbon fiber coated with a nano-SiO2 particle in a cement paste matrix, the present study proposed a method of coating nano-SiO2 particles on the surface of the carbon fiber by the chemical reaction of a silane coupling agent (glycidoxypropyltrimethoxysilane, GPTMS) and colloidal nano-SiO2 sol in an alkaline environment. To verify whether a nano-SiO2 particle was effectively modified on the surface of the carbon fiber, the surface morphology, chemical composition, and chemical structure were characterized and analyzed by several techniques such as the scanning electron microscope (SEM), energy-dispersive spectrometer (EDS), and Fourier-transform infrared spectroscopy (FT-IR). Nano-SiO2 particles were entirely covered and uniformly distributed on the surface of the carbon fiber, resulting in the formation of a thin layer of nano-SiO2 particles. A thin layer of nano-SiO2 particles reacted with Ca(OH)2 to form a calcium-silicate-hydrate (C-S-H) gel, which is most helpful to increase the form between the fiber and the matrix. In addition, a pull-out test of the tow carbon fibers was performed to verify the effect of the new surface modification method on the interfacial bond properties of the carbon fiber embedded in the cement paste matrix. The experimental results showed that the frictional bond strength of the carbon fiber coated with a nano-SiO2 particle was significantly increased compared to the plain carbon fiber. These results were expected to improve the interfacial bonding force of hardened cement paste from the formation of the C-S-H gel produced through the chemical reaction of nano-SiO2 particles coated on the surface of the carbon fiber with Ca(OH)2. In particular, it was confirmed that the carbon fiber-reinforced cement paste (CFRCP) specimens coated with a nano-SiO2 particle and silica fume which replaced 10 wt.% of cement by mass showed the highest pull-out resistance performance at 28 days of age. The new surface modification method developed in this study can be very beneficial and helpful in improving the interfacial bond properties of CFRCP.